Pengaruh Penerapan Total Quality Management Terhadap Efisiensi Biaya Kualitas - Abi Hamdani; Irsutami Irsutami (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2015)
This study is conducted with the aim to observe influence of total quality management (TQM) toward the efficiency cost of quality in manufacturing companies in Batam city, based on the perception of employees. The analysis technique used is multiple linear regressions with associative research method. This study include 6 subvariable of TQM which is focused on the customer, obsession on quality, teamwork, continuous improvement, training and education and empowerment and influence employee engagement measured through multiple regression test, f test, t test, and r2 test. The results of the study indicate weak correlation between sub variable TQM individually to the efficiency of the cost of quality, the conclusion drawn based on the statistical results is to focus on customer, obsession on quality, teamwork, continuous improvement, training and education and the empowerment and involvement of employees does not affect the partial and simultaneously to increase the efficiency of the cost of quality.